TITIK TOLAK EPISTEMOLOGIS FILSAFAT ALAM SEMESTA IMMANUEL KANT - Miska M. Amien (Jurnal Filsafat "WISDOM", 2007)
Immanuel Kant denied metaphysical thought. According to Kant, men are not able to understand the nature of something but phenomena. So also in terms of the universe, men can not attain the nature of universe but phenomena that rose from universe. In this context, Kant denied traditional cosmology. However, Kant develops his own cosmology. He talks about the origin of cosmos. Although the origin of cosmos can not retrace clearly, but it is able to understood by nebular theory. Kant explained space and time base on epistemological principles. Space and time are an image in human mind, they rose in the same time, and the other things came later.